A High‐Resolution Paleosecular Variation Record for Marine Isotope Stage 6 From Southeastern Black Sea Sediments. Issue 3 (23rd March 2021) - Nowaczyk, Norbert R.; Liu, Jiabo; Plessen, Birgit; Wegwerth, Antje; Arz, Helge W.
Abstract: A full‐vector paleosecular variation (PSV) record (inclination, declination, and relative paleointensity) from the pen‐ultimate glacial (130–180 ka) could be constructed from a total of 12 sediment cores recovered from the Arkhangelsky Ridge in the SE Black Sea. Stacking of the individual partly fragmented records was achieved by a detailed correlation using high‐resolution data records from X‐ray fluorescence scanning, Ca/Ti and K/Ti log‐ratios, as well as magnetic susceptibility. Age constraints are provided by a detailed composite oxygen isotope stratigraphy from three of the cores, correlated to U‐Th‐dated speleothem oxygen isotope records from Hungary and Turkey. The temporal resolution of the stacked paleomagnetic data records is 200 years. Practically, this data set is the first high‐resolution PSV record for SE Europe/SW Asia from marine isotope stage 6, comprising inclination, declination and relative paleointensity. Besides an easterly swing in declination at ∼159 ka and a pronounced intensity low together with low inclinations at ∼148 ka, both not reaching an excursional PSV index of >0.5, the obtained directional variations reflect only normal PSVs, with a PSV index of <0.3. Key Points: Reconstructed geomagnetic field variation record between 180 and 130 ka from Black Sea sediments First full‐vector paleosecular variation record from marine isotope stage 6 for Southeast Europe/Southwest Asia Intensity maxima occur at 166.5 ka and at 141.0 ka